Zooplankton in Breiðafjörður: Annual variability in community composition, abundance and fecundity - Vigdís Sigurðardóttir 1984- (2012)
Insights into life cycles of zooplankton, their fecundity and energy requirements, provides essential information for better understanding of energy transfer through trophic levels in the marine ecosystems. Zooplankton abundance, community composition and developmental stages of individual species of zooplankton were monitored at two locations in Breiðafjörður, West Iceland, in the summers of 2007-2009. This study revealed that the abundance of zooplankton varied between years with decreasing annual mean abundance in the three years, where the abundance in 2009 was six times lower than in 2007. The timing and magnitude of the maximum in abundance in 2007 resembled copepod life cycles of norhtern areas, such as Disco Bay and Tromsø, while the life cycles reflected southern areas, such as The Faroe Islands and the Western Channel in England in 2008 and 2009. Additionally, the feeding and fecundity parameters egg production and gut content (quantified as chlorophyll a) were measured for the two most abundant species of copepods, Temora longicornis and Calanus finmarchicus in 2008- 2009. Gut content and egg production of T. longicornis were not correlated with phytoplankton concentration, which indicates that the females did not base their egg production solely on the phytoplankton standing stock. The gut content of C. finmarchicus in Breiðafjörður was positively correlated with chlorophyll a concentration, while egg production rate was not. Egg production rates were positively correlated with the gut content. Thus, the chlorophyll a concentration might not be the limiting factor for the egg production rate and other factors, such as dinoflagellates, flagellates and ciliates might be limiting the female egg production rate. Þekking á lífsferlum dýrasvifs, tímgun þeirra og orkuþörf, eykur skilning á orkuflutningi milli fæðuþrepa í vistkerfi sjávar. Fylgst var með þéttleika dýrasvifs, samfélagsgerð og þroskunarstigum einstaka tegunda krabbaflóa á tveimur stöðvum í Breiðafirði sumurin 2007-2009. Helstu niðurstöður ...